Chronic hepatitis C virus in the state of Piauí, northeastern Brazil - Veras,Kelson Nobre (2009)
Knowledge of genotype distribution of hepatitis C virus (HCV) has clinical importance due to genotype 1 lower response to treatment compared with genotypes 2 and 3. The goal of this survey was to describe clinical and laboratorial profiles of patients with chronic hepatitis C (CHC) in the State of Piauí, as well as to expand the overall awareness of the distribution of HCV genotyping in Northeast of Brazil. A retrospective cross-sectional study was carried out between April 1999 and August 2005. A total of 153 patients were included, 119 (77.8%) males and 34 (22.2%) females; mean age = 48.01 ± 9.11 years. We observed a homogeneous distribution between genotypes 1 (50.0%) and 3 (49.0%), while the most frequent subtype noticed was 3a (49.0%). The mean viral load among patients with subtype 1b (1,232,476 UI/mL) was significantly superior to the subtype 1a (391,204 UI/mL; p = 0.010) and to the subtype 3a (594,228 UI/mL; p = 0.047). The average levels of gamma-glutamiltransferase of genotype 1 (144 mg/dL) had statistical differences when compared to genotype 3 (74 mg/dL; p = 0.014). Most patients showed mild to moderate degrees of histopathological necroinflammatory activity and hepatic fibrosis (79.0% and 56.2%, respectively). We concluded that most candidates to treatment of CHC in the State of Piauí presented with clinically stable hepatic illness; the distribution of genotypes 1 and 3 was virtually homogeneous; and there was no significant demographic or clinical differences among genotypes or subtypes of HCV.